(untitled) (Research, Society and Development, 2022)
The invention of automobiles is undoubtedly one of the best technologies that has fostered the capacity of a means of transport for human beings. However, accidents involving these means, called automobile trauma (AT), represent a public health problem due to their high morbidity and mortality associated, which even show an estimated increase until the year 2030. However, , in Brazil, there is a tendency to decrease AT rates, possibly related to current public and educational policies. The article in question aims to discuss prevention and aspects related to AT, emphasizing their relevance and investigating better approaches in an attempt to reduce this public health problem. It is, therefore, an integrative literature review, which used parameters such as: theme identification; determination of inclusion and exclusion criteria for articles; analysis and interpretation of information duly extracted from the sample; presentation of the review and synthesis of the formulated knowledge. For the construction of the sample, the importance of selecting the studies carried out in the last 10 years and the consideration of studies that show different aspects involved in the AT, such as the use of psychoactive substances and the main age group involved, was emphasized. The present study, therefore, suggests that the proper prevention of EDs is not only aimed at the legislative sphere, but also confers an educational duty, involving epidemiological aspects such as socioeconomic profile and age group.